A 5‐year prospective study on the clinical and aesthetic outcomes of alveolar ridge preservation and connective tissue graft at the buccal aspect of single implants. (5th November 2018) - Eghbali, Aryan; Seyssens, Lorenz; De Bruyckere, Thomas; Younes, Faris; Cleymaet, Roberto; Cosyn, Jan
Abstract: Aim: To evaluate the 5‐year aesthetic outcome of single implants following alveolar ridge preservation (ARP) and connective tissue graft (CTG) at the buccal aspect. Materials and Methods: Thirty‐seven periodontally healthy non‐smoking patients received flapless tooth extraction, ARP with a deproteinized bovine bone mineral with 10% collagen (DBBMC), implant placement (4–6 months later), a provisional screw‐retained crown and CTG at the buccal mucosa (3 months later) and a permanent crown (3 months later). The aesthetic results were the primary outcome and the clinical results the secondary outcome of the study. Both outcomes were compared to those after 1 year. Mucosal thickness (MT) was registered using a non‐invasive ultrasonic device. Results: Thirty‐two patients attended the 5‐year re‐assessment, and all implants survived. Mean marginal bone loss was 0.53 mm at 1 year and 0.47 mm at 5 years ( p = 0.439). Mesial Papilla showed a further re‐growth between 1 and 5 years ( p = 0.043). Mid‐facial recession amounted to 0.05 mm and 0.12 mm at 1 and 5 years, respectively ( p = 0.161). The Pink Esthetic Score was 11.00 and 11.17 at 1 and 5 years, respectively ( p = 0.596). MT gain amounted to 0.97 mm (relative stability: 90.5%) and 0.91 mm (relative stability: 85%) at 1 and 5 years, respectively ( p = 0.249). Conclusion: ARP and CTG resulted in favourable clinical and aesthetic outcomes. CTG substantially increased MT with acceptable stability over a 5‐year period.